MODEL ALIRAN STEADY NON UNIFORM (Studi kasus pada sungai Bedog Daerah Istimewa Yogyakarta) - Ratna Septi Hendrasari (Universitas Negeri Yogyakarta, 2012)
The river is the lowest part of the earth’s surface in the form of groovesextending from upstream toward downstream. Flow characteristics was influencedby the morphology condition. Flow Modelling was performed as a first step to find outthe flow characteristic. The aim of the research is to identify the flow characteristicsof river. The research was conducted in reaches of Bedog river, from Pendowo weiras upstream boundary to Kadisono weir as downstream boundary. SoftwareQUAL2K was applied in the modelling. The modelling was conducted in dry seasonand wet season. The Bedog river was devided into 10 reaches with each crosssectional area was simplified to trapezium type. The Manning roughness was usedas tool of calibration and verification in flow modelling. The stream roughness, thatrepresented by the Manning roughness in steady non uniform flow, considering themorphology condition and flow characteristic, including depth and velocity. TheManning roughness due to the flow modelling was not the same with the trueManning roughness to nature. This condition was caused by flow modellingmechanism.